(untitled) (Research, Society and Development, 2023)
This article presents definitions and novel data on four different ways to operationalize political instability: coups d’etat, constitutional endurance, chief executive turnover, and completed executive terms. We cover nineteen Latin American countries since independence until 2005, thus compiling a dataset of country-year observations. Additionally, we code the years in which -independently of regime type- some modicum of political opposition was allowed. The data reveals high levels of intra and inter country heterogeneity, but we are able to offer a periodization of general patterns of regional instability over the past two centuries. First, after independence Latin Americans faced a long period of institution building that was highly unstable. Second, the last decades of the nineteenth century witnessed remarkable improvements in terms of political stability. Third, military coups challenged the incipient history of stability around 1930. Fourth, after 1980 the trend is towards stability. Finally, political pluralism existed in two thirds of the observations in the dataset. The analysis of the evolution of opposition and completed terms across countries is indicative, however, of intra regional heterogeneity.